ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI KELAPA DI DESA MALONAS KECAMATAN DAMPELAS KABUPATEN DONGGALA - Deli Yanti; Rukavina Baksh; Dance Tangkesalu (Universitas Tadulako, 2015)
This Research intent to know how big coconut farmer income and to know coconut farmer feasibilty at Malonas vilage Kecamatan Dampelas Kabupaten Donggala. The Determination of the location of the Research carried out deliberately with the consideration that the Village Malonas is one of coconut production Center. This Research was funded from April to May. Respondents in this study is the coconut farmers in the Malonas Village Dampelas Subdistrict Donggala Regency Sampel teke in observational it by methodics sampel random sampling, total respondents farmer that was taken from by this Research as big as 30 respondents of 110 coconut farmer that is at malonas vilage, it uses income analisis, properness analisis and description analisis. Result average revenue obtained in the coconut farmers as big as Rp.2.007.816/0,63ha/MP or 3.187.002/ha/MP and ratio analisis with value R/C as big as 2,45. Its mean Beach Rp 1.000 cost expenditure will get acceptance as big as Rp. 2.450.